Integrazione in Europa. Un’esplorazione empirica tra vincoli strutturali e reazioni contestuali - Gozzo, Simona; Lombardo, Elisa (SocietàMutamentoPolitica, 2020)
The paper highlights the dynamics related to the problem of the integration of immigrants in Europe, focusing on the spread of prejudices and on the multiple conditions of exclusion. The main aim refers to the effectiveness of integration policies implemented in Europe. For this purpose, data from different sources are analysed to measure the degree of hostility versus tolerance towards foreign immigrants, both through official data and with the analysis of online comments published on Twitter during the period of European elections.